Per Ulrik Stenhammar i sin samtid - Ekström, Christina (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2023)
With the goal of shedding new light on a person who has come to be overshadowed by his famous son, Wilhelm Stenhammar, the aim of this study is to identify the musical activities of Per Ulrik Stenhammar (1829–1875), an architect by profession. Questions addressed are: In which musical roles does Per Ulrik Stenhammar appear? Which environments are included in his musical activities? Which aesthetic choices can be identified? The study has a biographical approach. The orientation is agent-structuralism, a perspective which focuses the interaction between the agent and the structure, seeing them as inextricably integrated. The study uses content analysis as method. The empirical data material consists of published and unpublished compositions, personal letters, notes and sketches, family chronicles, correspondence and newspapers. The result shows that in addition to being a composer, Per Ulrik Stenhammar was also an instrumentalist and a singer, that he was involved in both confessional and art-musical environments, and that his musical activities were based on a theologically motivated aesthetic. Examples of areas for future research identified in this study are Stenhammar’s string quartets and the interface between the different aesthetic expressions in his work in the two artistic disciplines of music and architecture. Keywords: Per Ulrik Stenhammar, biographical approach, confessional and art-music environments, public and private spaces, theologically motivated aesthetics.